Avaliação dos efeitos induzidos pela carboximetil-glucana (CM-G) sobre o sistema cardiovascular de ratos normotensos e hipertensos - Galvão, Alynne Carvalho (2021)
Hypertension is a highly prevalent disease worldwide, being characterized by a multifactorial clinical condition. In this context, this study study was designed to investigate the effects of a newly synthesized carboxymethyl-glucan (CM-G) on blood pressure (BP), baroreflex sensitivity (BRS) and sympathetic vascular modulation in renovascular hypertensive rats. Male Wistar rats were divided into four groups: SHAM+SALINE, 2K1C+SALINE (subjected to renal artery clipping to induce renovascular hypertension); SHAM+CM-G (treated with CM-G) and 2K1C+CM-G (treated with CM-G). The daily treatment with CM-G (40 mg/kg) was performed for 2 weeks. Blood pressure, heart rate (HR), systolic BP variability, baroreflex sensitivity (BRS) and sympathetic vascular tone were evaluated. After six weeks of renal artery clipping, 2K1C rats exhibited arterial hypertension (171 ± 11 vs. 118 ± 4 mmHg, p < 0.05), impaired BRS (−1.30 ± 0.10 vs. −2.59±0.17 bpm.mmHg-1, p < 0.05) and enhanced sympathetic activity by 81% when compared to sham rats. Oral administration of CM-G in renovascularhypertensive rats reduced hypertension (126 ± 4 vs. 171 ± 11 mmHg, p < 0.05) and improved the BRS (−2.03±0.16 vs. −1.30 ± 0.10 bpm.mmHg−1, p < 0.05) in 2K1C rats when compared to placebo. Those effects seem to be caused by a reduction in sympathetic activity. Besides, hypertensive rats have greater contraction to phenylephrine (126.60% ± 2.97% vs. 95.24% ± 5.49%; p < 0.05), which was restored by CM-G treatment (90.26% ± 8.54%vs. 95.24% ± 5.49%; p > 0.05). Furthermore, vasorelaxation to acetylcholine and sodium nitroprusside was diminished in hypertensive rats, which was also restored by CM-G. Finally, oral treatment with CM-G reduced serum levels of malondialdehyde, an important biomarker used in the assessment of oxidative stress, in treated hypertensive animals when compared to untreated animals (14.62 ± 0.93 vs. 21.82 ± 1.27 nmol/ml, p ˂ 0,05). The present study revealed for the first time that treatment with CM-G reduced arterial hypertension and restored baroreflex sensitivity through a reduction in sympathetic tone, in addition to normalizing vascular reactivity and reducing oxidative stress in rats with renovascular hypertension.